Pengembangan Aplikasi Penentuan Rute Pengiriman Barang Berdasarkan Berat dan Time Windows Menggunakan Metode Nearest Neighbour dan Tabu Search - Purwadana, Putu Irvan Arya; Candiasa, I Made; Sukajaya, I Nyoman (Majalah Ilmiah Teknologi Elektro, 2021)
One of practical example of CVRPTW is delivery. Important factors in delivery are cost, speed, service and consistency. In order for these factors to be met optimally, the capacity and time windows must be considered. Capacity affects service and consistency, so the right route must be choosen with the shortest distance and the right capacity. Time windows affects on the speed and costs so that the delivery must be carried out according specified time and company operating hours. This research purpose to produce delivery routes that consider capacity and delivery time. There are two steps in calculation, which is clustering and searching of optimal delivery route. The clustering step uses a polar angle and the optimal route searching uses the nearest neighbour and the tabu search. The test show that the delivery route generated by the system can make efficiency distance of 12.18%, time of 5.54% and capacity of 1.27% and cost of 12.18%.